2019
DOI: 10.22213/2410-9304-2019-1-144-151
|View full text |Cite
|
Sign up to set email alerts
|

Constructional and Thermal Insulation Material Based on High-Strength Anhydrite Binder

Abstract: Исследованы физико-механические свойства конструкционно-теплоизоляционной композиции на основе высокопрочного ангидритового вяжущего, приготовленного на основе фторангидрита - отхода производства плавиковой кислоты - и вспученного перлитового песка. Для активации процессов структурообразования ангидритового вяжущего использовался 3%-й водный раствор фосфата натрия Na3PO4. В качестве сверхлегкого заполнителя в композиции использовался вспученный перлитовый песок. Проведенные исследования микроструктуры и рентге… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The obtined dispersion was then used to create an electrically conductive composite based on the waste product of hydrofluoric acid -fluorohydrite [16]. Sodium phosphate [11] was used as an activator of fluorohydrit. This led to a double increase in the strength characteristics of the composite in comparison with known traditional activators [1], such as sodium sulfate, etc.…”
Section: Methodsmentioning
confidence: 99%
“…The obtined dispersion was then used to create an electrically conductive composite based on the waste product of hydrofluoric acid -fluorohydrite [16]. Sodium phosphate [11] was used as an activator of fluorohydrit. This led to a double increase in the strength characteristics of the composite in comparison with known traditional activators [1], such as sodium sulfate, etc.…”
Section: Methodsmentioning
confidence: 99%
“…Dispersion analysis (Yakovlev et al, 2019a) showed that the average particle size of the expanded perlite sand is 65 μm, up to 72% of the particles of the expanded sand have sizes up to 100 μm. The average particle diameter is 10.5 μm.…”
Section: Methodsmentioning
confidence: 99%
“…The aim of this study was to increase the physico-mechanical characteristics of fluoroanhydrite compositions to expand their field of use. In the course of the work, the effect of a plasticizer based on an aqueous solution of polycarboxylate esters on the properties of high-strength and lightweight expanded pearlite sand compositions based on technogenic anhydrite (Yakovlev et al, 2019a), namely, fluoroanhydrite, a waste product of hydrofluoric acid, was studied.…”
Section: Introductionmentioning
confidence: 99%